The Value of Vocational Education : High School Type and Labor Market Outcomes in Indonesia - Newhouse, David; Suryadarma, Daniel (World Bank, 2013)
This paper examines the relationship between the type of senior high school attended by Indonesian youth and their subsequent labor market outcomes. This topic is timely in light of a recent policy shift that aims to dramatically expand vocational education. The analysis controls for an unusually rich set of predetermined characteristics, and exploits longitudinal data spanning fourteen years to separately identify cohort and age effects. There are four main findings. First, the estimated wage premium for vocational graduates, relative to general graduates, is greater for women than men. Second, the returns to public vocational school for men have plummeted for the most recent cohort, and male vocational graduates now face a large wage penalty. Third, the generally favorable outcomes of public school graduates can be partly explained by non-random sorting of students with higher test scores and better-educated parents into public schools. Finally, these peer effects appear to be particularly important for students with above-average test scores, as men with high scores earn a surprisingly small premium from graduating from vocational or private general school. These small returns for high-scoring men, as well as the dramatic fall in the earnings premium for all male vocational graduates, raise important concerns about the current expansion of public vocational education and the relevance of the male vocational curriculum in an increasingly service-oriented economy.